Investigate the Immuno-Histological Changes of Renal Tissue in Alloxan Induced Diabetic in Albino Male Rats Treated with Ethanolic Herbal Extract (Moringa oleifera seeds) - Kadhim, Fateh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Aim: This study aimed to assess the nephron-protective effect of Moringa oleifera seeds extract against alloxan induced diabetic male rats. The seeds of Moringa oleifera, have long been utilized in traditional medicine and as a source of nutritional supplements in various parts of the world. Numerous studies have been published highlighting the pharmacological properties of M. oleifera seeds (MOS), which encompass the ability to lower blood glucose levels and reduce inflammation. Nevertheless, the mechanisms that underlie its therapeutic effects is not well understood. Therefor this study was designed to define the alterations that may occur in response to MOS use. Methods: The present study comprised a total of eighteen adult albino male rats, which were split into three groups (A, B, and C), each consisting of six rats. Diabetes was induced in two groups (B and C) using alloxan at a dosage rate of 150 mg/kg body weight intraperitoneally following a pre-induction fast period of 24 hours. While, group (A) served as (Normal Control) was administered normal saline. After confirming the incidence of diabetes, the treatment was started as follows: Group A and B (negative and positive control) received no treatment. Whereas. Group C received 100 mg/kg/day of Moringa oleifera seeds extract orally for 21 consecutive days. The levels of serum IL-6 were analysed. Pathological tissue damage was assessed using Periodic Acid-Schiff staining. The presence of CD3T cells was detected through IHC. Results: in comparison to the DN group, the experimental rats treated with MOS exhibited a remarkable reduction in serum IL-6 levels and kidney tissue damage. Furthermore, the MOS extract led to a decrease in CD3 expression. Conclusion: Overall, this study suggests that ethanolic extract of MOS could inhibit IL-6 synthesis and the infiltration of T cells, which leads to delay the development of DN by improving the outcomes of the kidney.